(untitled) (Research, Society and Development, 2021)
This study aims to conduct a literature survey about the Impacts of mastectomy on women’s self-image and sexual life. This is an integrative literature review, were search occurred in the Virtual Health Library (VHL), with the help of the databases Latin American and Caribbean Literature on health sciences (LILACS), Nursing Database (BDENF), Scientific Eletronic Library Online (SciELO) and PUBMED. The articles were colleted from may to june 2021, being used the descriptors: Mastectomy, Self image and Women. After applying the inclusion criteria, 13 studies remainde. The present study shows that the breasts are considered a symbol for female sexuality, and that when faced with a diagnosis of breast cancer, women experience negative feelings such as despair, sadness, annoyance, fear of death, uncertainty, anxiety, fear, among others. Such feelings are associated with cancer as a disease that encompasses several negativities and proportionally affects the woman’s life expectancy.